An Evaluation of Northern Bobwhite Conservation Research: A Call for Large-Scale Studies - Lex J. Gomez; Kelly S. Reyna (National Quail Symposium Proceedings, 2017)
Northern bobwhite (Colinus virginianus) populations have declined throughout the species’ range since the 1960s. Habitat loss and degradation are thought to have largely contributed to this decline by reducing the amount of space and resources required to sustain viable quail populations. Previous studies have attempted to address this issue by focusing on ranch-level management of bobwhites instead of on the effectiveness of large-scale techniques. Here, we review current and historical studies that have facilitated the implementation of management techniques on multiple scales. In doing so, we will also reveal the shortcomings of such studies by highlighting their narrowed focus on small-scale management and research, and reiterate the need for large-scale studies.
Keywords: colinus virginianus; northern bobwhite; conservation; habitat evaluation; population ecology; research practices; scale